(untitled) (Bangladesh Journal of Infectious Diseases, 2019)
Background: Post-operative wound infection may occur after routine abdominal surgery. Objective: The purpose of the present study was to see the distribution and determinants of post-operative wound infection among the patients underwent routine abdominal surgery. Methodology: This non-randomized clinical trial was conducted in the different surgical units of the Department of Surgery at Sir Sallimullah Medical College & Mitford Hospital, Dhaka, Bangladesh during January 2001 to December 2002 for a period of two (02) years. In the operation theatre, after anaesthesia skin was cleaned with Povidone iodine USP 5% w/w or Spirit (70% methylated spirit in water) or Chlorhexidine. During post-operative period dressing were left undisturbed unless it was felt necessary. Unusual pain in and around the wound was considered to be an indication of infection. A swab was taken from any discharge and was sent for bacteriological examination. Result: In this study, 50 patients were admitted as routine cases and undergone routine abdominal operations in general operation theatre. Out of 50 patients undergone routine abdominal surgery, 5 developed wound infection post operatively. Overall infection rate was 10.0%. In routine abdominal operations, infection was 9.09% in upper midline or extended midline incision, 33.33% in lower midline, 6.25% right subcostal/Kocher’s. In routine abdominal operations, the rate of infection in clean contaminated wound was 11.11%, contaminated wound was 33.33%. Wound infection rate was 20.0% cases in patients with malnutrition, 14.28% cases in obesity and 16.66% cases in diabetes mellitus. Conclusion: In conclusion post-operative wound infection is common in routine surgical operation. Bangladesh Journal of Infectious Diseases, June 2019;6(1):16-21